2013
DOI: 10.1074/jbc.m113.486050
|View full text |Cite
|
Sign up to set email alerts
|

Leucine-rich Repeat and Immunoglobulin Domain-containing Protein-1 (Lrig1) Negative Regulatory Action toward ErbB Receptor Tyrosine Kinases Is Opposed by Leucine-rich Repeat and Immunoglobulin Domain-containing Protein 3 (Lrig3)

Abstract: Background: Lrig1 is a negative regulator of oncogenic receptor tyrosine kinases. Results: Lrig3 opposes Lrig1 negative regulatory action and enhances ErbB receptor stability. Conclusion: Lrig1 and Lrig3 oppose one another. Significance: Despite structural homology, Lrig1 and Lrig3 are functionally distinct.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 35 publications
4
41
3
Order By: Relevance
“…LRIG mutations with a high impact score according to Mutation Assessor are shown in in Table 1. High impact mutations are localized exclusively to the extracellular domain which is not unexpected given the conservation of this region of LRIGs and the requirement of the extracellular domain for recognition of interacting partners (Gur et al ., 2004, Rafidi et al ., 2013). …”
Section: Lrig Expression In Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…LRIG mutations with a high impact score according to Mutation Assessor are shown in in Table 1. High impact mutations are localized exclusively to the extracellular domain which is not unexpected given the conservation of this region of LRIGs and the requirement of the extracellular domain for recognition of interacting partners (Gur et al ., 2004, Rafidi et al ., 2013). …”
Section: Lrig Expression In Cancermentioning
confidence: 99%
“…Recently, deletion analysis of LRIG1 led to the finding that Δ-cyto LRIG1 (lacking the entire cytoplasmic domain which contains the c-Cbl binding site) is fully active in mediating ErbB2 degradation (Rafidi et al ., 2013), underscoring the existence of a c-Cbl independent mechanism for LRIG1. This is supported by the prior finding that Δ-cyto LRIG1 and wild type LRIG1 have similar abilities to inhibit the growth of glioma cells (Yi et al ., 2011).…”
Section: Lrig Mechanism Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note Recently, Colleen Sweeney and Lisa V Goodrich reported that overexpression of LRIG3 in HEK293T cells increased the ERBB receptor expression (Rafidi et al, 2013). However, downregulation of LRIG3 in a human glioblastoma cell line, GL15, resulted in upregulation of total EGFR and phospho-EGFR, and enchanced glioma cell proliferation, adhesion and invasion .…”
Section: To Be Notedmentioning
confidence: 99%
“…The gene LRIG1 (leucine-rich repeat and immunoglobulin domain-containing protein-1) has been found to be a tumor suppressor gene (Rafidi et al, 2013). Research has shown that the mRNA and protein expression of this gene were reduced in a variety of tumor cells, including pituitary tumor cell lines and pituitary tumor tissue, compared with normal tissue.…”
Section: Introductionmentioning
confidence: 99%